ALGORITHM OF DIAGNOSTICS AND TREATMENT OF ELDERLY AND SENILE PATIENTS WITH ACUTE CHOLECYSTITIS, CHOLEDOCHOLITHIASIS AND OBSTRUCTIVE JAUNDICE - M. D. Dibirov; G. S. Rybakov; V. L. Domarev; M. A. Vasilyeva; B. M. Brodetsky; M. V. Kosachenko (Неотложная медицинская помощь)
We performed a retrospective analysis of treatment in 4,197 patients with acute cholecystitis. Destructive complicated cholecystitis was diagnosed in 658 (25.3%) patients . There were 431 (65.5%) patients of elderly and senile age. All patients had comorbidities. Cardiovascular insufficiency — 73.9%, respiratory diseases — 29.2%, diabetes — 26%. For urgent indications, 12 (2.8%) patients were operated, 2 (16.6%) of them died. In 419 (97.2%) patients, mini-invasive treatment was performed. Endoscopically, jaundice wasn’t managed in 86 (20.5%) cases. In 62 (14.8%) cases, percutaneous transhepatic microcholangiography was performed under ultrasound guidance. Laparoscopic cholecystectomy was performed in 183 (43.6 %) cases, traditional cholecystectomy was performed in 149 (35.6%) cases, and in 38 of them (23.9%) it was combined with Kerr’s drainage of choledoch. Mini-invasive cholecystectomy was performed in 87 (20.7%) cases. Postoperative complications were revealed in 21 (5.0%) patients, in 7 (2.9%) of elderly age and 14 (7.9%) of senile age. Postoperative mortality rate was 2.0%. The use of minimally invasive interventions in the complex treatment of this group of patients was the main goal and it was reasoned by the severity of the initial condition of elderly and senile patients.